2018
DOI: 10.1177/2042098618784809
|View full text |Cite
|
Sign up to set email alerts
|

Using EMR-enabled computerized decision support systems to reduce prescribing of potentially inappropriate medications: a narrative review

Abstract: Prescribing of potentially inappropriate medications (PIMs) that pose more risk than benefit in older patients is a common occurrence across all healthcare settings. Reducing such prescribing has been challenging despite multiple interventions, including educational campaigns, audits and feedback, geriatrician assessment and formulary restrictions. With the increasing uptake of electronic medical records (EMRs) across hospitals, clinics and residential aged care facilities (RACFs), integrated with computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 68 publications
1
75
0
2
Order By: Relevance
“…Given the increasing uptake of electronic prescribing and medical records, potential exists for electronic clinical decision support systems (CDSSs) to enhance deprescribing at the point of care. A recent narrative review identified 20 studies investigating the use of CDSSs to reduce inappropriate medication use . While the evidence suggests a benefit of these types of systems, particularly in the hospital setting, there is limited robust work on the development and implementation of such tools.…”
Section: Tools To Aid the Overall Process Of Deprescribingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing uptake of electronic prescribing and medical records, potential exists for electronic clinical decision support systems (CDSSs) to enhance deprescribing at the point of care. A recent narrative review identified 20 studies investigating the use of CDSSs to reduce inappropriate medication use . While the evidence suggests a benefit of these types of systems, particularly in the hospital setting, there is limited robust work on the development and implementation of such tools.…”
Section: Tools To Aid the Overall Process Of Deprescribingmentioning
confidence: 99%
“…A recent narrative review identified 20 studies investigating the use of CDSSs to reduce inappropriate medication use. 36 While the evidence suggests a benefit of these types of systems, particularly in the hospital setting, there is limited robust work on the development and implementation of such tools. Several CDSSs have been specifically developed to enhance and guide deprescribing activities.…”
Section: Electronic Clinical Decision Support Systemsmentioning
confidence: 99%
“…Icotinib is a primary research drug in China, and studies have shown that it is as effective as the other EGFR‐TKI first‐generation drugs . Compared with cisplatin, nedaplatin, a cisplatin derivative, has fewer toxic effects, higher response rate and longer overall survival, especially in patients with squamous carcinoma . If WFO was able to output these two alternative treatments as “recommended” or “for consideration,” the overall consistency could be elevated from 73.3% to 90.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described strategies to address polypharmacy have demonstrated variable efficacy, [12][13][14][15][16] with interventions led by pharmacists having the greatest success. We used the tool to facilitate deprescribing in acute care for the following reasons: polypharmacy is common in this population where the average number of drugs can exceed 10 20 ; hospitalization provides a unique point of contact with the healthcare system and can involve specialists with familiarity in managing polypharmacy; electronic decision support for reducing PIMs has shown promise in the acute care setting 21 ; and finally, there is a unique opportunity to engage patients and/or families in deprescribing because they may be both a "captive audience" and motivated to stop medications that may have contributed to the hospitalization. [17][18][19] In this study (NCT02918058), we tested MedSafer, a Canadian-made electronic decision support tool for deprescribing (www.medsafer.org).…”
mentioning
confidence: 99%